Stuck in Transition : Reform Experiences and Challenges Ahead in the Kazakhstan Power Sector - Aldayarov, Mirlan (Washington, DC: World Bank, 2016)
The large-scale transformation of Kazakhstan’s power sector following independence in 1991 was reflected by the country’s move toward liberalizing the market and implementing sector regulation. As an early adopter of a liberalized multimarket model consisting of bilateral, spot, balancing, ancillary, and capacity submarkets Kazakhstan’s power sector was regarded a market reform leader among countries of the former Soviet Union, having achieved a much improved supply and demand balance and service quality.